Perception of School Committee Members (SCMs) on Factors Contributing to Overweight and Obesity Among High School Students in Kiribati: A Qualitative Study - Tong, Tanebu J.; Mohammadnezhad, Masoud; Alqahtani, Nasser Salem; Salusalu, Mosese (Frontiers in Public Health, 2022)
Background: Schools are vital settings for overweight and obesity prevention among children and adolescents. School Committee Members (SCMs) are crucial assets to engaging students with overweight and obesity prevention programs. This study aimed to determine factors contributing to overweight and obesity among high school students in Kiribati through the perception of SCMs. Methods: This prospective qualitative study was conducted in four (4) randomly selected senior high schools on South Tarawa, Kiribati from August to November 2020. With purposive selection of twenty (20) SCMs employed at the four (4) high schools, both males and females, and consented to participate in the study. A semi-structured open-ended questionnaire was used for data collection using focus group discussions (FGDs). Data was transcribed and analyzed using thematic analysis method. Results: Twenty (20) participants were involved in FGDs with equal number of SCMs (n=5) who attended FGDs for each school and 45% of which were females. Six themes identified were knowledge, behaviors, and perceived status towards overweight and obesity, perceived action benefits, perceived barriers to practices, proposed strategies to overweight and obesity prevention. These themes reveal that SCMs have a broad understanding and skill set for overweight and obesity causes and effect. However, the aptitude alone is not enough to prevent the occurrence thus proposed feasible plans were voiced for responsible stakeholders to include in policy developments for overweight and obesity prevention. Conclusion: This study recognized that knowledge-behavior gap is the main reason behind the failure in preventative strategic approaches among adolescents. As role models to students, SCMs and their schools should team up in implementing the public health policies and building mutual awareness and understanding with students and other specialist stakeholders for a more momentous and viable impact.